Dampak Perkembangan Pariwisata Terhadap Struktur Lanskap Di Kecamatan Kuta Selatan, Kabupaten Badung, Bali - Krisnandika, Anak Agung Keswari; Yusiana, Lury Sevita; Fitriana, Devvy Alvionita (Jurnal Arsitektur Lansekap; Vol. 10, No. 2 Oktober 2024, 2024)
The Impact of Tourism Development on Landscape Structure in South Kuta District, Badung Regency, Bali. South Kuta District is one of the sub-districts in Badung Regency, Bali, which is located in a coastal area and is a tourism center. Its presence in a coastal area makes this subdistrict rich (ecosystem services) and vulnerable (change, damage and loss) simultaneously. As a tourism center, development in South Kuta District increases from year to year, especially in the tourist accommodation sector. This development development causes changes in the landscape structure. This research aims to analyze changes in landscape structure that occur and analyze the influence of tourism aspects on changes in landscape structure. The methods used in this research are spatial analysis, binary logistic regression analysis and SBE analysis. Spatial analysis is used to analyze landscape structure (patches) and its changes using Landsat 7 ETM+ imagery for 2010 and Landsat 8 OLI imagery for 2022. Binary logistic regression analysis to analyze the influence of tourism aspects on changes in landscape structure. The tourism aspect used is tourist accommodation data (lodging, restaurants, banking and health centers). Scenic Beauty Estimation (SBE) analysis is used as an assessment of areas experiencing changes in landscape structure. The urgency of this research is to prevent or minimize the impact of ecological damage from tourism development, especially the decline in environmental and visual quality due to changes in landscape structure that occur in South Kuta District.